Endoscopic third ventriculostomy - experience of 16 cases - Rahman, Aminur; Rahman, Md Zillur; Islam, Manzoorul; Rahman, Asifur; Sultan, Majed (Journal of Chittagong Medical College Teachers' Association, 2009)
Key words: endoscopic third ventriculostomy; obstructive hydrocephalus doi: 10.3329/jcmcta.v19i2.3867 Journal of Chittagong Medical College Teachers' Association 2008: 19(2):27-32